BPG: Seamless, automated and interactive visualization of scientific data - P’ng, Christine; Green, Jeffrey; Chong, Lauren C.; Waggott, Daryl; Prokopec, Stephenie D.; Shamsi, Mehrdad; Nguyen, Francis; Mak, Denise Y. F.; Lam, Felix; Albuquerque, Marco A.; Wu, Ying; Jung, Esther H.; et al. (BMC bioinformatics, 2019)
Background We introduce BPG, a framework for generating publication-quality, highly-customizable plots in the R statistical environment. Results This open-source package includes multiple methods of displaying high-dimensional datasets and facilitates generation of complex multi-panel figures, making it suitable for complex datasets. A web-based interactive tool allows online figure customization, from which R code can be downloaded for integration with computational pipelines. Conclusion BPG provides a new approach for linking interactive and scripted data visualization and is available at http://labs.oicr.on.ca/boutros-lab/software/bpg or via CRAN at https://cran.r-project.org/web/packages/BoutrosLab.plotting.general